MO141: Antibody Response against SARS-COV-2 in Dialysis Patients During COVID-19. (3rd May 2022) - Christian Østergaard, Hans; Mose, Frank; Lauridsen, Thomas G; Randers, Else
Abstract: BACKGROUND AND AIMS: Patients in haemodialysis are a vulnerable group, thought to have a poor antibody response to vaccination. In Denmark dialysis, patients were one of the first patient groups to be vaccinated against COVID-19. By investigating the antibody response of dialysis patients, we will gain unique knowledge about the vaccine efficacy in this group. METHOD: The study is a multicentre observational trial involving the dialysis departments of three Danish hospitals: The Regional Hospital Holstebro, the Regional Hospital Viborg and Aalborg University Hospital. All patients had blood samples taken before vaccination (baseline) and three blood samples every third month after vaccination to evaluate the antibody response.  COVID-19 antibodies where analysed with Sandwich ELISA technique, which is a routine analysis at the Department of Clinical Microbiology in Aarhus University Hospital with a lowest limit of detection at 4.8 Bau/mL and limit of detection at 2080 Bau/mL. Antibody levels are reported as medians with interquartile range. Non-parametric comparison was performed to evaluate differences. RESULTS: A total of 219 patients with chronic kidney failure in haemodialysis were included. Of the 219, 11 (5%) had positive COVID-19 PCR tests prior to baseline blood sampling. However, at baseline prior to vaccination only 6 of 219 (3%) had antibodies higher than the lowest detectable limit of 4.8. Baseline medians were 4.8 (4.8; 4.8) and 9.55 (4.81; 51.5) for all patients and for patients with positive COVID-19 test respectively. Two of the six (33%) patients with confirmed prior COVID infection and with no significant antibody levels were in immunosuppressive treatment.  At first sample after vaccination, 35 of 219 (16%) patients had no detectable antibody titer. Overall titre median was 318 (41.7; 985.7). In the above, no distinction was made between those fully vaccinated and those with only 1 dose at the time of the first sample. When only regarding the antibody response of those double vaccinated at first sample, the median is 563.5 (158.5; 1130).  For those with COVID-19 infection prior to vaccination, the median titre was 2080 (1900; 2080) at first sample after vaccination.  Of the 219, 30 (13.7%) patients were in active immunosuppressive therapy at baseline, at first sample median in this group was lower at 86 (20; 194) ( P  < .05 compared to patients not on immunosuppression).  In the second and third sample after vaccination, taken approximately 3 and 6 months after vaccination, the overall medians were 165(44.4; 385) and 69.4 (20;181) respectively ( P  < .05 versus before vaccination for both samples). For patients with prior infection, the medians were 1815 (1302; 2080) and 1590 (698.8;2080) respectively ( P  > .05 versus before vaccination and P  < .05 versus patients without prior infections regarding both samples).  The patients in immunosuppressing therapy had a median of 26 (10.3; 127.2) and 14.6 (7.8; 43) in second and third sample, respectively.  Eight fully vaccinated patients had no antibody response above limit of detection, three of these (38%) were in ongoing treatment with immunosuppressive medication. No correlations were found between antibody response and comorbidity or cause of renal impairment. CONCLUSION: This study shows that 211 of 219 dialysis patients have a positive antibody response to the COVID vaccines. Those infected prior to vaccination had a greater response in all the samples. Few patients had low antibody response, some of these were in immunosuppressive treatment. Patients treated with immunosuppressive therapy had a significantly lower antibody response compared to patients not in treatment with this.